Empowering MSMEs Through Product Branding Innovation and Rengginang Location Digitalization: A Case Study in Mainan Village - Pratiwi , Imanda Ajeng; Akbar , M. Alif; Wulandari, Siska; Alie, Juhaini; Munandar, Aris; Ghina, Aliah (Golden Ratio of Data in Summary, 2025)
Empowering Micro, Small, and Medium Enterprises (MSMEs) is a strategic agenda for driving inclusive economic growth in Indonesia. This study explores MSME empowerment strategies through rengginang product innovation in Mainan Village. Using a descriptive qualitative approach and case studies, the research highlights various aspects of product development, marketing digitalization, and branding strategies. The results show that product innovation, packaging, and the use of digital technology can improve business competitiveness and sustainability. Continuous mentoring, multi-stakeholder collaboration, and a locally-based approach are key factors in the success of MSME empowerment in this village.